Cross-country differences in the effects of oil shocks - Gert Peersman; Ine van Robays (Center for Economic Studies and ifo Institute (CESifo), 2010)
We compare the economic consequences of several types of oil shocks across a set of industrialized countries that are structurally very diverse with respect to the role of oil and other forms of energy in their economy. We find considerably different effects across countries, which crucially depend on the underlying source of the oil price shift. For oil demand shocks driven by global economic activity and oil-specific demand shocks, all countries experience respectively a temporary increase and transitory decline of real GDP following the oil price increase. The role of oil and other forms of energy seems not to matter to explain cross-country differences for the consequences of both shocks. This role, however, is very important to explain asymmetries in the effects of exogenous oil supply shocks. Whereas net oil and energy-importing countries all face a permanent fall in economic activity, the impact is insignificant or even positive in net energy-exporting countries. In addition, countries that improved their net energy-position the most over time, became less vulnerable to oil supply and oil-specific demand shocks, relative to other countries.
Keywords: E31; E32; Q43; 330; oil prices; vector autoregressions; cross-country differences; Mineralölpreisschock; Makroökonomischer Einfluss; Industriestaaten; Welt